Association of nicotine dependence and gut microbiota: a bidirectional two-sample Mendelian randomization study - Chen, Yuexuan; Zhao, Mengjiao; Ji, Kaisong; Li, Jingjing; Wang, Shuxin; Lu, Liming; Chen, Zhenhu; Zeng, Jingchun (Frontiers in Immunology, 2023)
Background: Nicotine dependence is a key factor influencing the diversity of gut microbiota, and targeting gut microbiota may become a new approach for the prevention and treatment of nicotine dependence. However, the causal relationship between the two is still unclear. This study aims to investigate the causal relationship between nicotine dependence and gut microbiota. Methods: A two-sample bidirectional Mendelian randomization (MR) study was conducted using the largest existing gut microbiota and nicotine dependence genomewide association studies (GWAS). Causal relationships between genetically predicted nicotine dependence and gut microbiota abundance were examined using inverse variance weighted, MR-Egger, weighted median, simple mode, weighted mode, and MR-PRESSO approaches. Cochrane's Q test, MR-Egger intercept test, and leave-oneout analysis were performed as sensitivity analyses to assess the robustness of the results. Multivariable Mendelian randomization analysis was also conducted to eliminate the interference of smoking-related phenotypes. Reverse Mendelian randomization analysis was then performed to determine the causal relationship between genetically predicted gut microbiota abundance and nicotine dependence. Results: Genetically predicted nicotine dependence had a causal effect on Christensenellaceae (β: -0.52, 95%